Pengaruh Penggunaan Media Elektronik di Kalangan Santri dalam Mencapai Keberhasilan Belajar - Nurisma, Atsmim Lana; Taulabi, Imam; Ubaidila, Syafik (Universitas Islam Tribakti Lirboyo Kediri, 2025)
It is undeniable that at this time technology has developed very rapidly. Various kinds of electronic media were created to facilitate human affairs such as television, mobile phones, tablets, laptops, computers, and so on. With the development of the times, there is nothing wrong with starting to use electronic media as a learning resource, even though electronic media is seen as having many disadvantages but there are great benefits if electronic media can be used as well as possible. Darussalam Lirboyo Kediri Islamic Boarding School is one of the Islamic boarding schools that allows students to use electronic media as a source of media for learning. This study uses a quantitative approach, the number of samples is 50 students using purposive sampling. The research instrument uses a scale, namely the electronic scale media, with a reliability value of = 0.872 and a learning success scale with a reliability value of = 0.926. The results of this study are (1) the level of use of electronic media among students at the Pondok Pesantren Putri Unit Darussalam Lirboyo Kediri has a moderate level of use of electronic media that is 38%, (2) The rate of learning success among students at the Pondok Pesantren Putri Unit Darussalam Lirboyo Kediri Has a level of moderate, namely 42%, (3) There is an influence of the use of electronic media on the success of learning among students at the Pondok Pesantren Putri Darussalam Lirboyo Unit Kediri. which is evidenced by the slight influence between the use of electronic media on learning success that is equal to 18.1%.